Numerical simulation study of solar cell - Soufia Abdelhafid; Soufia Raid Abdelhafid (University of Shahid Hama Lakhdar - El Oued, 2025)
"A numerical simulation study of solar cells employs computational techniques to model and analyse the behaviour of solar cells under various operating conditions. By solving physical equations governing charge carrier transport, light absorption, and electrical performance, these simulations provide valuable insights into the internal mechanisms of solar cells. The approach enables the optimization of design parameters, such as material properties, layer thickness, and doping concentration, to maximize efficiency. Furthermore, numerical simulations allow for the prediction of solar cell performance, offering a cost- effective and time-efficient alternative to experimental trial-and-error methods. This study emphasizes the importance of numerical simulations in advancing solar cell technology and accelerating the development of high-performance photovoltaic devices. "تستخدم دراسة محاكاة عددية للخاليا الشمسية تقنيات حسابية لنمذجة وتحليل سلوكها تحكم نقل حامالت ت ي يائية ال ي ظل ظروف تشغيل متنوعة. ومن خالل حل المعادالت الف يز ز ف مة حول اآلليات ّ ، توفر هذه المحاكاة رؤى قي ي الشحنة، وامتصاص الضوء، واألداء الكهربائ ية للخاليا الشمسية. ويتيح هذا النهج تحس يز الداخل معاي يالتصميم،مثل خصائص المادة، التشويب، لتحقيق أقىص قدر من الكفاءة. عالوة عىل ذلك، تتيح وسمك الطبقة، وترك يز من حيث التكلفة ً فعاال ً المحاكاة العددية التنبؤ بأداء الخاليا الشمسية، مما يوفر بديال والوقت ألساليب التجربة والخطأ التجريبية. وتؤكد هذه الدراسة عىل أهمية المحاكاة تطوير تكنولوجيا الخاليا الشمسية وترسي ع تطوير األجهزة الكهروضوئية عالية ي ز العددية ف األداء.."
Master's theses: specializing in wired and non-wired communications
Keywords: Numerical Simulation Solar Cells InGaP (Indium Gallium Phosphide) SCAPS-1D Software Photovoltaic Devices Charge Carrier Transport Light Absorption Electrical Performance Bandgap Engineering Doping Concentration Layer Thickness Optimization Tandem Solar Cells Photovoltaic Efficiency Semiconductor Materials Energy Conversion; المحاكاة العددية الخلايا الشمسية الإنديوم غاليوم فوسفيد (InGaP) برنامج SCAPS-1D الأجهزة الكهروضوئية نقل حاملات الشحنة امتصاص الضوء الأداء الكهربائي هندسة فجوة الطاقة تركيز التطعيم (التشويب) تحسين سماكة الطبقات الخلايا الشمسية متعددة الوصلات كفاءة الخلايا الشمسية المواد شبه الموصلة تحويل الطاقة